Effect of pond size and number of feeder hoppers on the productivity of the shrimp Penaeus vannamei fed with acoustic technology in a semi-intensive shrimp farm in Ecuador: Efecto del tamaño del estanque y el número de tolvas alimentadoras en la productividad del camarón Penaeus vannamei alimentado con tecnología acústica en una camaronera semi-intensiva de Ecuador - Valle Masson, Juan Carlos (2025)
ABSTRACT | The productivity of a shrimp farm in the Province of Guayas (Ecuador) was studied by analyzing 400 production cycles in 32 ponds of 7-27 ha, using acoustic feeders associated with several hoppers.  The results indicate an improvement in production during the last years, and productive advantages in ponds of less than 10 ha The effect on production of the different laboratories supplying larvae has been confirmed, which suggests the convenience of choosing the origin of the post-larvae appropriately. In relation to the optimal number of feeders, the best results were obtained with 2,0 hectares per feeder, but a controlled study is necessary to obtain definitive conclusions.